Pendidikan Kesehatan Batuk, Pilek Dan Pijat Common Cold Dalam Upaya Mengatasi Ketidakefektifan Bersihan Jalan Napas Pada Balita - Baidah, Baidah; Ariani, Sri Purwanti; Nahdi, Rafi’an Al (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
Cough and cold symptoms are indicative of respiratory system disturbances that commonly affect toddlers (1-5 years old). Respiratory disorders, or Acute Respiratory Infections (ARIs), are a leading cause of mortality in children. The disease can quickly spread to others through droplets, and its transmission is particularly rapid during the current rainy season due to the weakened immune systems of toddlers. However, parents often perceive coughs and colds as common occurrences, leading them to neglect providing treatment to their children. This becomes problematic when children experience respiratory distress, prompting confusion among parents who then rush their children to the hospital. The community engagement activities involve interactive lectures and training sessions, including role-playing with phantom children, for 15 mothers with toddlers. The activities are conducted over a period of two weeks in Alalak Island RT 3. The mothers' knowledge is assessed before and after the sessions through questionnaires. To evaluate the effectiveness of the common cold massage technique, observations are made following established Standard Operating Procedures (SOPs). The results of the community engagement show an improvement in knowledge levels before and after health education. Regarding the common cold massage technique, a small percentage can perform the procedure directly, while the majority can follow the SOPs using phantom children. It is hoped that the increased knowledge and skills of mothers will enable them to promptly address cough and cold symptoms in their children.